Comparison of the Streptozyme Test with the Antistreptolysin O, Antideoxyribonuclease B, and Antihyaluronidase Tests - Klein, George C. (1971)
The streptozyme test was compared with the antistreptolysin O (ASO), antideoxyribonuclease B (ADN-B), and antihyaluronidase (AH) tests. One hundred and twenty-seven human serum specimens were tested by each of the four tests. The streptozyme test detected more specimens with elevated titers than any single test; however, it was not as effective as the combination of the ASO and ADN-B tests. The streptozyme test appears to be particularly useful for laboratories which rely solely on the ASO test for serological evidence of a streptococcal infection. The test can be used in these laboratories to screen all specimens with low ASO titers (<170) for the detection of ADN, AH, antinicotinamide adenine dinucleotidase, and antistreptokinase.